4 - The Debate on Quality and the Private Surge: A Status Review of Private Universities and Colleges in Tanzania - Ishengoma, Johnson M (Journal of Higher Education in Africa, 2007)
While enrolments in private universities is still low in Tanzania, their number, however, is surging at an alarming rate raising critical questions about their aca- demic quality in terms of their course offerings and the qualifications of the aca- demic staff involved in teaching these programmes. Despite this surge in the sheer number of Tanzania private universities, public universities remain dominant in terms of enrolment. This paper (i) documents the hitherto-lacking critical infor- mation about private universities and university colleges in Tanzania, (ii) dis- cusses the implications of the surge and (iii) discusses the related issues of aca- demic quality.